Strategi LILA Pengelolaan Bahan Makanan Dengan Status Gizi (IMT dan LILA) Pada Ibu Hamil Dan Wus Dengan Risiko KEK Di Desa Sukasari Kec.Air Periukan Kab.Seluma - Herpinta, Neni Suci; Sari, Liya Lugita; Munawaroh , Mei; Yani, Gustri (Utami Publisher, 2025)
Chronic Energy Deficiency (CED) is a significant contributor to maternal morbidity and mortality, particularly among pregnant women and women of reproductive age. In Seluma Regency, Bengkulu Province, the incidence of CED is a growing concern. Specifically, in Dusun 1, Sukasari Village, contributing factors include short birth intervals, physically demanding activities, inadequate nutritional intake, monotonous eating patterns, and low nutrition literacy.The 2025 Thematic Community Service Program (KKN-T) of Dehasen University Bengkulu focuses on the prevention of CED and reduction of stunting risk through educational approaches. The strategies employed include CED counseling, food management training, body mass index (BMI) and upper arm circumference (MUAC) measurements, distribution of educational leaflets, and digital nutrition education.This program is part of the KKN-T initiative implemented through counseling sessions, hands-on practice, and digital education. The target population includes residents of Dusun 1, Sukasari Village. Key topics covered are understanding CED, managing food ingredients, and conducting BMI and MUAC measurements. Evaluation was carried out by observing community participation and field outcomes. The results showed an increase in public awareness regarding the importance of balanced nutrition, proper birth spacing, BMI and MUAC monitoring, and proper food management. These efforts aim to reduce the incidence of CED among pregnant women and women of reproductive age.The program proved effective as a community-based promotive and preventive strategy and may serve as a model for implementation in other regions. Cross-sector collaboration and ongoing education are essential to support the reduction of CED cases and contribute to stunting prevention by improving maternal health.